Ethics in Advertisements & Its Impact on Consumer Psychology-A Study of Patiala Region - Singh, Harpreet (Prabandhan: Indian Journal of Management, 2008)
Advertising is one of the most potent weapon of promotion in the marketing mix. The companies are expected to make neat and effective advertisements that should appeal to the audience in a positive way and influence them to buy the products. But the actual picture is not like this. Most of the advertisements these days are unethical in nature. The overall corporate industry does not adhere to clear ethical standards as laid down my ASCI. Lack of strong code of professional conduct results in companies not able to distinguish correctly between what is morally right and wrong, instead focusing solely on making money.With the increase in competition and consumers becoming more variety seekers, companies keep on creating attractive advertisements to woo the viewers. Sometimes these contain sexual content that one can't see with the children. On other occasions these advertisements hurt the sentiments of people belonging to a particular religion. This study is aimed at finding the psychology of people regarding use of unethical advertising and its ultimate effect on their buying behaviour.